Passive sampling of environmental DNA in aquatic environments using 3D‐printed hydroxyapatite samplers. (18th March 2022) - Verdier, Héloïse; Konecny‐Dupre, Lara; Marquette, Christophe; Reveron, Helen; Tadier, Solène; Grémillard, Laurent; Barthès, Amélie; Datry, Thibault; Bouchez, Agnès; Lefébure, Tristan
Abstract: The study of environmental DNA (eDNA) released by aquatic organisms in their habitat offers a fast, noninvasive and sensitive approach to monitor their presence. Common eDNA sampling methods such as water filtration and DNA precipitation are time‐consuming, require difficult‐to‐handle equipment and partially integrate eDNA signals. To overcome these limitations, we created the first proof of concept of a passive, 3D‐printed and easy‐to‐use eDNA sampler. We designed the samplers from hydroxyapatite (HAp samplers), a natural mineral with a high DNA adsorption capacity. The porous structure and shape of the samplers were designed to optimize DNA adsorption and facilitate their handling in the laboratory and in the field. Here we show that HAp samplers can efficiently collect genomic DNA in controlled set‐ups, but can also collect animal eDNA under controlled and natural conditions with yields similar to conventional methods. However, we also observed large variations in the amount of DNA collected even under controlled conditions. A better understanding of the DNA–hydroxyapatite interactions on the surface of the samplers is now necessary to optimize eDNA adsorption and to allow the development of a reliable, easy‐to‐use and reusable eDNA sampling tool.